Rancang bangun early warning system pada perlintasan sebidang berbasis mikrokontroller dengan lora dan SMS gateaway - Ramadhan, Rahmat Putra; Puspitasari, Mariana Diah; PEW, Agustinus (Jurnal Teknik Industri Terintegrasi (JUTIN), 2024)
Level crossings between roads and railway tracks in Indonesia still face significant safety challenges. According to the Indonesian Minister of Transportation Regulation Number 94 of 2018, an automatic early warning system without guards is required. Some locations, such as those under the supervision of the Madiun Service Unit and the Class 1 Surabaya Railway Technical Center, have been equipped with systems made by PT Wantech, but many are non-functional. This study aims to create a microcontroller-based early warning system using LoRa and SMS Gateway technology as a temporary replacement. Using the waterfall method and mean absolute error, this study compares the HC-SR04 and HY-SRF05 ultrasonic sensors. The results show that HY-SRF05 is superior in detecting trains, with an average data transmission time of 2.5 seconds for distances up to 1.5 km using LoRa, and the SMS Gateway successfully sent warning notifications at the same distance. This system is expected to improve the safety of road users and train journeys